Bracket creep revisited - with and without r>g: Evidence from Germany - Junyi Zhu (Deutsche Bundesbank, 2015)
Using German income distribution in 2009, this paper studies the redistributive and revenue effects of bracket creep under various inflation scenarios. We develop a tax micro-simulation model for the newly available Panel on Household Finance (PHF) data. The simulation yields an inverted U-shaped overall redistributive effect of the income tax and social insurance contribution system with respect to the inflation rate, which contrasts with Immervoll (2005) who finds that fiscal drag always enhances the equalising effect. The nominal income growth as well as the deterioration of tax progression at the middle and top of the income distribution between 1998 and 2009 can be the impetus for this change. This result implies that delaying adjustment might reduce redistribution. We also suggest that these results might not be restricted solely to Germany. Additionally, when we introduce the empirical evidence that capital income grows faster than non-capital income 􀝎 > 􀝃, the dual tax system with a flat capital income tax implemented in 2009 further disequalises the after-tax income substantially. Allowing inflation compensation to lean towards the poor by boosting their share of capital income may not be favourable to redistribution.
Keywords: C81; H24; D31; H23; 330; Inflation; Fiscal Drag; Progressivity of Income Tax; Income Distribution; Microsimulation; Capital income taxation